2020
DOI: 10.1093/ofid/ofaa014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Safety Evaluation of Continuously Infused Ceftolozane/Tazobactam in the Outpatient Setting

Abstract: Background Ceftolozane/tazobactam (C/T) is a novel cephalosporin/β-lactamase inhibitor currently dosed by 8-hour intervals to treat complicated and multidrug-resistant Pseudomonas aeruginosa infections in inpatients. This dosing strategy limits the ability to transition patients to outpatient antimicrobial therapy. There are limited data in the literature to support continuous infusion (CI) dosing. Methods This study is a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), [ 21 , 22 , 24 , 27 29 , 33 , 34 , 39 41 , 43 45 , 50 , 51 , 54 , 56 , 57 , 59 , 61 , 62 , 68 71 , 73 – 77 , 79 – 85 , 87 – 92 , 94 , 95 , 97 – 100 ] Spain (N = 15) [ 26 , 28 , 30 32 , 35 37 , 42 , 47 , 49 , 58 , 66 , 79 , 96 ], and Italy (N = 13) [ 18 , 20 , 23 , 25 , 48 , 52 , 53 , 55 , 64 , 67 , 72 , 79 , 86 ]. A variety of study designs were captured: 27 were non-comparative retrospective studies [ 18 , 19 , 22 , 24 , 25 , 28 , 32 , 33 , 40 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), [ 21 , 22 , 24 , 27 29 , 33 , 34 , 39 41 , 43 45 , 50 , 51 , 54 , 56 , 57 , 59 , 61 , 62 , 68 71 , 73 – 77 , 79 – 85 , 87 – 92 , 94 , 95 , 97 – 100 ] Spain (N = 15) [ 26 , 28 , 30 32 , 35 37 , 42 , 47 , 49 , 58 , 66 , 79 , 96 ], and Italy (N = 13) [ 18 , 20 , 23 , 25 , 48 , 52 , 53 , 55 , 64 , 67 , 72 , 79 , 86 ]. A variety of study designs were captured: 27 were non-comparative retrospective studies [ 18 , 19 , 22 , 24 , 25 , 28 , 32 , 33 , 40 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
“…(range): 14 (7–35) days 95 (18/19) 74 (14/19) 21 (4/19) Buonomo et al 2020 [ 20 ] Retrospective, single center case series Italy 4 PsA (50% MDR; 50% XDR) cSSTI in patients with chronic kidney disease - Dose C/T: creatine clearance adjusted (100.0%)—0.75 g q8h (75%), 0.375 g q8h (25%) Empiric C/T: 0.0% Confirmed C/T: 100.0% Duration: med. (range): 14 (14) days 100.0 (4/4) - 0 Jones et al 2020 [ 21 ] Retrospective single center, case series US 7 PsA (57.1% non-MDR; 42.9% MDR) infections (one patient also had an E. coli infection), including pneumonia (42.9%), cUTI (28.6%), and bacteremia (14.3%) Dose C/T: 4.5 g qd (CI; 85.7%), 9 g qd (CI; 14.3%) Duration: med. (range): 14 (6–42) days 85.7 (6/7) 100.0 (3/3) 0 a Jorgensen et al 2020 [ 22 ] Retrospective, multicenter US 259 MDR gram-negative infections (91.1% PsA; 23.2% Enterobacterales) including, RTIs (62.9%), SSTIs (10.8%), and UTIs (10.0%).…”
Section: Resultsmentioning
confidence: 99%
“…Ceftolozane-tazobactam can be administered in continuous infusion, and it is stable for up to 24 hours at room temperature, allowing for potential administration as a continuous infusion by elastomeric pumps. In a study published recently, 7 patients were treated with ceftolozane-tazobactam in continuous infusion in the outpatient setting, and 6 of 7 patients had symptom resolution [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outpatient parenteral antimicrobial treatment (OPAT) is an alternative for these infections but generally requires several injections per day, and elastomeric pumps are a good alternative. In reference to an article published in your journal recently by Jones, Huelfer, and Bland [ 1 ], we present a case of Pseudomonas aeruginosa osteomyelitis treated with surgery and antibiotic therapy with ceftolozane-tazobactam in continuous infusion at home using an elastomeric pump.…”
mentioning
confidence: 99%
“…Cefiderocol is only stable for four hours at room temperature and is not currently stable for use in OPAT [ 27 ]. A small case series has used infusions of ceftolozane-tazobactam over 24 hours in OPAT with good outcomes [ 28 ]. However, stability studies have shown ceftolozane-tazobactam to be stable for only 12 hours at 32 °C [ 29 ].…”
Section: Discussionmentioning
confidence: 99%